2015
DOI: 10.1155/2015/192742
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Risk Management in Malaysian Construction Industry: Case Studies

Abstract: Construction industries are exposed to wide array of risks, such as financial, design, and contractual ones, which might have a direct impact on their performance toward achieving the desired objectives. Risk Management is a proactive decision-making process used to minimize and manage the risks in the most efficient and appropriate manner. However, most construction firms in Malaysia do not apply formal risk management in their projects. Thus, this study aims to identify the actual process of risk management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
(13 reference statements)
1
34
0
Order By: Relevance
“…Landscape projects predominate all the activities in a typical landscape architecture's organisation as it determines the survival of the organisation's portfolio. The dynamic and unique nature of projects create multiple project risks that needs to be managed to assure project objectives are achieved (Akintoye & MacLeod, 1997;APM, 2012;Mills, 2007;Ng & Loosemore, 2007;PMI, 2017), which by failure of doing so results to financial loss, affects organisation's reputation that could contribute to loss of business in the future (Algahtany, Alhammadi, & Kashiwagi, 2016;Hamzah Abdul-Rahman, Chen Wang, 2015). Hence, the conceptual framework proposes for the RMP to be integrated into a landscape PLC procedure to assure that project risks are managed systematically.…”
Section: Project Level: Rmp Integration Into Landscape Plcmentioning
confidence: 99%
See 1 more Smart Citation
“…Landscape projects predominate all the activities in a typical landscape architecture's organisation as it determines the survival of the organisation's portfolio. The dynamic and unique nature of projects create multiple project risks that needs to be managed to assure project objectives are achieved (Akintoye & MacLeod, 1997;APM, 2012;Mills, 2007;Ng & Loosemore, 2007;PMI, 2017), which by failure of doing so results to financial loss, affects organisation's reputation that could contribute to loss of business in the future (Algahtany, Alhammadi, & Kashiwagi, 2016;Hamzah Abdul-Rahman, Chen Wang, 2015). Hence, the conceptual framework proposes for the RMP to be integrated into a landscape PLC procedure to assure that project risks are managed systematically.…”
Section: Project Level: Rmp Integration Into Landscape Plcmentioning
confidence: 99%
“…A project risk management is beneficial for projects to enhance project performance through precise systematic management of project risks (Cooper, Grey, Raymond, & Walker, 2005;Hillson, Grimaldi, & Rafele, 2006; and has since been integrated as part of the project management process (APM, 2012;PMI, 2017). Several studies of PRM benefits by Abdul-Rahman, Wang, & Sheik Mohamad (2015); Jusoff, Yusuwan, Adnan, & Omar (2008); Kang, Fazlie, Goh, Song, & Zhang (2015); Mills (2007); PMI (2017); and provide an understanding of the risk management application in projects have been reviewed to improve chances of reaching project performance objectives and provide better control over the future outcome of the project. However, further study is carried out by Adnan (2008); Goh & Abdul-Rahman (2013); Hamzah Abdul-Rahman, Chen Wang (2015); Jusoff, Yusuwan, et al (2008); Kang et al (2015); and Mohamed, Abd-Karim, Roslan, Mohd Danuri, & Zakaria (2014) in the attempt to guide towards understanding and practicing PRM in Malaysia in the context of construction.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been remarkable efforts toward risk management in construction projects, implementation of risk management process is still inadequate. Studies [5,[21][22][23][24][25] have documented risk management practice in the construction industry. Akintoye & MacLeod [23] found that risk analysis and management in construction depend mainly on intuition, judgment and experience.…”
Section: Risk Management In Constructionmentioning
confidence: 99%
“…Mahendra et al [25] determined that the participants used to handle the risks with an informal approach because of less knowledge and awareness among the construction industry stakeholders. Similarly, Abdul-Rahman et al [21] found that the implementation of risk management process in Malaysian construction industry is still at a low level, due to the fact that most of the construction employees involved in risk management are not fully aware of the available risk management techniques that can be applied in construction projects. Kikwasi [24] also noted inadequate risk management knowldege among consultants and determines that most consultants use document reviews and assumptions to identify risks and contingency sum method to quantify risks.…”
Section: Risk Management In Constructionmentioning
confidence: 99%
“…The available risk response strategies together with their variants are traced in a number of studies [6][7][8][9][10][11][12][13][14]. Collectively, these strategies can be summarised as risk avoidance, reduction/mitigation, transfer/sharing, retention/acceptance.…”
Section: Introductionmentioning
confidence: 99%